2021
DOI: 10.1002/ece3.7968
|View full text |Cite
|
Sign up to set email alerts
|

Effects of consumer surface sterilization on diet DNA metabarcoding data of terrestrial invertebrates in natural environments and feeding trials

Abstract: DNA metabarcoding is an emerging tool used to quantify diet in environments and consumer groups where traditional approaches are unviable, including small‐bodied invertebrate taxa. However, metabarcoding of small taxa often requires DNA extraction from full body parts (without dissection), and it is unclear whether surface contamination from body parts alters presumed diet presence or diversity. We examined four different measures of diet (presence, rarefied read abundance, richness, and species composition) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 61 publications
2
14
0
Order By: Relevance
“…The hepatopancreas retained prey DNA sequences longest, followed by the mid-gut. This result finds support in similar studies conducted in spiders, where the opisthosoma (the tagma containing the mid-gut and the hepatopancreas) was the best body part to detect DNA of the consumed prey (Krehenwinkel et al, 2017;Macías-Hernández et al, 2018;Miller-ter Kuile et al, 2021).…”
Section: Gut Portion Selectionsupporting
confidence: 83%
“…The hepatopancreas retained prey DNA sequences longest, followed by the mid-gut. This result finds support in similar studies conducted in spiders, where the opisthosoma (the tagma containing the mid-gut and the hepatopancreas) was the best body part to detect DNA of the consumed prey (Krehenwinkel et al, 2017;Macías-Hernández et al, 2018;Miller-ter Kuile et al, 2021).…”
Section: Gut Portion Selectionsupporting
confidence: 83%
“…We removed mussel individuals from the sediment and used sterile razor blades to collect a single biofilm sample from the shell of each mussel. Blades were rinsed with 90% ethanol, wiped with a sterile kimwipe, and flame sterilized for 1 min between samples ( Horton et al, 2019 ; Miller-ter Kuile et al, 2021 ). Five shell samples did not successfully sequence (three from A. ligamentina and two from A. plicata ) resulting in a final n of 19.…”
Section: Methodsmentioning
confidence: 99%
“…These species respond in composition, diversity, diet and abundance to productivity in this system [15,32]. In this study, we examined trophic patterns for a spider top predator, Heteropoda venatoria , and for spider intermediate predators Keijia mneon , Scytodes longipes and Neoscona theisi , which are all common, habitat generalist, intermediate predator species on the atoll and are predated by H. venatoria [29,30].…”
Section: Methodsmentioning
confidence: 99%
“…We also considered guano, rather than marine wrack, as a second-end source for (a) only consumers from high-productivity sites and (b) all consumers and found that isotopic trophic position stayed the same. Original explanations of sample processing for diet DNA data are in [29,30], although we adjusted bioinformatics filtering steps that were overly conservative from that original study to capture greater diet diversity, especially among predators. Specifically, while we originally removed all other predator species sequences from any sample that was run on the same sequencing run as those shared species, this step was likely overly conservative given that we followed best practices for both laboratory sample preparation and post-sequence filtering based on negative control samples [34].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation